2017
DOI: 10.1111/ejn.13661
|View full text |Cite
|
Sign up to set email alerts
|

Trait impulsiveness is related to smaller post‐commissural putamen volumes in males but not females

Abstract: Impulsivity is considered a vulnerability trait for addiction. Recently, we found trait non-planning impulsiveness measured with the Karolinska Scales of Personality was negatively correlated with dopamine D receptor availability in the ventral striatum of healthy humans. While also observed in rodents, human studies have failed to find this association with other measures of trait impulsivity. We explored whether another rodent finding, reduced ventral striatum volume with greater impulsivity, could also be o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 86 publications
1
17
2
Order By: Relevance
“…We did not find a relationship between BIS-11 scores and striatal gray matter volume in our data. The literature on gray matter volume and impulsivity is not consistent with two studies finding a negative relationship between striatal volume and trait impulsivity 63 , 92 , albeit in different subregions and using different personality scales, and another showing a positive correlation between caudate volume and behavioral impulsivity (from a temporal discounting task) 64 . The challenge of the structural literature is that there are multiple measures being used to assess different aspects of impulsivity, and this has at times limited the ability to replicate findings across studies and species.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…We did not find a relationship between BIS-11 scores and striatal gray matter volume in our data. The literature on gray matter volume and impulsivity is not consistent with two studies finding a negative relationship between striatal volume and trait impulsivity 63 , 92 , albeit in different subregions and using different personality scales, and another showing a positive correlation between caudate volume and behavioral impulsivity (from a temporal discounting task) 64 . The challenge of the structural literature is that there are multiple measures being used to assess different aspects of impulsivity, and this has at times limited the ability to replicate findings across studies and species.…”
Section: Discussionmentioning
confidence: 82%
“…We conducted exploratory analyses between gray matter volume of striatum and ventral tegmental area (VTA), FE-PE2I BP ND , and BIS-11 scores (see Supplemental Materials and Table S2 ). Previous research has found relationships between striatal gray matter volume and behavioral 63 , 64 and trait 92 impulsivity in human subjects. We did not find a relationship between BIS-11 scores and striatal gray matter volume in our data.…”
Section: Discussionmentioning
confidence: 94%
“…First, the sample was entirely male. Some studies carried out in healthy participants have found gender-related differences in impulsive tendencies 87 , choice impulsivity 88 and response impulsivity 89 . Future studies would benefit from including women and comparing both groups from a three-factor impulsivity perspective 8 .…”
Section: Discussionmentioning
confidence: 99%
“…We recently observed a negative correlation between D 2/3 R availability in the VS and trait impulsivity, measured using the Karolinska Scales of Personality (KSP), in healthy people [24]. Since lower D 2/3 R availability in the VS has been related to smaller VS volumes in rodents [26] and humans [27, 28], we explored whether trait impulsivity measured with the KSP was related to VS volumes in healthy humans [29]. While trait impulsivity was not significantly associated with VS volumes, in a post-hoc analysis we observed a significant sex-interaction in the post-commissural putamen.…”
Section: Introductionmentioning
confidence: 99%